2021
DOI: 10.5603/rpor.a2021.0006
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal-sparing total body irradiation with the use of helical tomotherapy for nonmalignant indications

Abstract: background: the aim was to demonstrate the feasibility and technique of gonadal sparing total body irradiation (tBi) with helical tomotherapy. total body irradiation is a common part of the conditioning regimen prior to allogeneic stem cell transplantation. Shielding or dose-reduction to the gonads is often desired to preserve fertility, particularly in young patients undergoing transplant for non-malignant indications. helical tomotherapy (ht) has been shown to be superior to traditional tBi delivery for orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In this study, the uterine dose was reduced to 7–7.6 Gy, suggesting that uterine dose reduction does not affect the course of pregnancy and delivery for patients who received TBI with ovarian shielding after puberty. Recent advances in TBI using intensity-modulated radiation therapy have enabled the radiation dose to the reproductive organs to be reduced to the idealized dose [ 18 ]. As more and more TBI using intensity-modulated radiation therapeutic techniques are expected to be performed in the future, further studies with a larger number of patients are warranted to determine the radiation dose to the reproductive organs to maintain normal pregnancy and childbearing processes in female survivors who have undergone TBI.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In this study, the uterine dose was reduced to 7–7.6 Gy, suggesting that uterine dose reduction does not affect the course of pregnancy and delivery for patients who received TBI with ovarian shielding after puberty. Recent advances in TBI using intensity-modulated radiation therapy have enabled the radiation dose to the reproductive organs to be reduced to the idealized dose [ 18 ]. As more and more TBI using intensity-modulated radiation therapeutic techniques are expected to be performed in the future, further studies with a larger number of patients are warranted to determine the radiation dose to the reproductive organs to maintain normal pregnancy and childbearing processes in female survivors who have undergone TBI.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Compared to a conformal 3D plan, modulated treatments (such as IMRT and VMAT) require the utilization of more MUs and are therefore less efficient in delivering the prescription dose, which consequently results in proportional increases in collimator scatter and head leakage [ 50 ]. However, if flattening-filter-free (FFF) beams are used, MUs will increase but gantry head leakage will decrease owing to the absence of the flattening filter, a major contributor to head leakage [ 52 ]. With the exception of neutron contribution, out-of-field doses vary little with beam energy or depth in the patient, except at the patient’s surface near the field edge [ 50 ].…”
Section: Strategies For Reducing Out-of-field Dosementioning
confidence: 99%
“…With the exception of neutron contribution, out-of-field doses vary little with beam energy or depth in the patient, except at the patient’s surface near the field edge [ 50 ]. Dibs et al demonstrated meaningful gonadal sparing with the use of helical tomotherapy for patients undergoing total body irradiation for nonmalignant indications [ 52 ].…”
Section: Strategies For Reducing Out-of-field Dosementioning
confidence: 99%